Nurk : the strange, surprising adventures of a (somewhat) brave shrew - Vernon, Ursula (Harcourt, 2008)
Nurk, a sort-of brave shrew, packs up a few pairs of clean socks and sails off on an accidental adventure, guided by wisdom found in the journal of his famously brave and fierce grandmother, Lady Surka the warrior shrew.